Relações genéticas entre plantéis de reprodutores do camarão marinho Litopenaeus vannamei, através do seqüenciamento dos genes RNAr 16S e COI do DNAmt - Francisco, Ana Karina de (Universidade Federal de São Carlos, 2003)
The evaluation of genetic relationships among broodstocks is a useful tool for culture management programs. In the present work, the relationships amongst four broodstocks of the marine shrimp Litopenaeus vannamei were established based on sequencing of 16S rRNA and COI regions from mtDNA. Farfantepenaeus subtilis was used as outgoup in mtDNA analysis. No divergence was found when sequences of the 16S rRNA gene were compared, likely due to the conservativeness of such region. Otherwise, at the dendrogram obtained from COI gene sequencing, clustering between Aqua-044 and Aqua-045 broodstocks and between Aqua-046 and Aqua-051 broodstocks was observed. The formation of these groupings may be related to the origin of the broodstocks as well as to the effects of genetic drift suffered by the founder populations. The results obtained in the present work may constitute a very useful tool for the delineation of more appropriate management programs for the analyzed broodstocks.
Keywords: Genética; Camarão; Distância genética; DNA; Mitocondrial; CIENCIAS BIOLOGICAS::GENETICA